DOES HIRNEOLA AURICULA-JUDAE OCCUR IN MALESIA? - D Rangkuti; Mien A Rifai (Research Center for Biology, 1974)
Examination of all collections of Hirneola, preserved in Herbarium Bogoriense indicates that Hirneola auricula-judae does not occur naturally in Malesia. Previous records of this species from this region are shown to be misdetermination.